2014
DOI: 10.1002/jqs.2739
|View full text |Cite
|
Sign up to set email alerts
|

The detailed tephrostratigraphy of a core from the south‐east Black Sea spanning the last ∼60 ka

Abstract: One visible volcanic ash layer and 21 non‐visible, cryptotephra horizons have been identified in the M72/5‐25‐GC1 core from the south‐east Black Sea that spans the last ∼60 ka. Glass chemistry suggests that the tephras derive from Italian, Hellenic and Turkish sources. The visible tephra layer is trachytic in composition and has been correlated to the ∼39 ka Campanian Ignimbrite super‐eruption from Campi Flegrei caldera, Italy. Two cryptotephra layers are associated with eruptions from Acigöl volcano (Turkey) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 89 publications
0
30
0
Order By: Relevance
“…Geochemical comparisons between different samples have been implemented with the help of more and more sophisticated statistical tools (Borchardt et al, 1972;Kutterolf et al, 2008a;Green et al, 2014;Bronk Ramsey et al, 2015b). It is possible that tephras from different (or similar) tectonic settings but originating from different geographical regions (e.g., different island arcs) can be found in the same geological sequence (e.g., Lane et al, 2011;Cullen et al, 2014). A practical guide on discrimination of glasses from different tectonic settings has been recently developed for Mediterranean, Icelandic and Azores volcanoes .…”
Section: Future Challenges and Perspectivesmentioning
confidence: 99%
“…Geochemical comparisons between different samples have been implemented with the help of more and more sophisticated statistical tools (Borchardt et al, 1972;Kutterolf et al, 2008a;Green et al, 2014;Bronk Ramsey et al, 2015b). It is possible that tephras from different (or similar) tectonic settings but originating from different geographical regions (e.g., different island arcs) can be found in the same geological sequence (e.g., Lane et al, 2011;Cullen et al, 2014). A practical guide on discrimination of glasses from different tectonic settings has been recently developed for Mediterranean, Icelandic and Azores volcanoes .…”
Section: Future Challenges and Perspectivesmentioning
confidence: 99%
“…What is more, one particular Alaskan tephra, the White River Ash (AD 833–850), has also been correlated to the well‐known AD 860B isochron identified in Ireland (Hall and Pilcher, ; Jensen et al , ) and beyond. Further afield, Cullen et al () demonstrate how Italian, Hellenic and Turkish tephras are preserved in a Black Sea core, opening up the possibilities for tracing tephras from these sources further east. Moreover, the discovery of fallout material from Pacific arc volcanoes in Greenland ice presents an exciting opportunity for Atlantic–Pacific correlations (Bourne et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…). Tephras from Roxolany (Wulf et al , ) and from Black Sea drill cores (Cullen et al , ) also have similar glass compositions. Using various bivariate major element plots, the Pantellerian Green tuff can be readily distinguished based on its high FeO content, which differs from other tephras.…”
Section: Discussionmentioning
confidence: 99%
“…the late Pleistocene Ciomadul volcano (Harangi et al , ; Szakács et al , ; Karátson et al , ; Molnár et al , , ). Tephra beds in the Black Sea drilling cores (Cullen et al , ), in loess deposits of Ukraine (Wulf et al , ) and in Middle Palaeolithic caves (Veres et al , ) have been recently suggested as derived from large explosive eruption events of Ciomadul volcano. However, to confirm this and to elucidate the regional impact of the Ciomadul eruptions, a better characterization of the Ciomadul tephras is necessary through geochronological, petrological and geochemical fingerprinting to constrain the accurate age and the nature of the volcanic products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation